PENINGKATAN HASIL BELAJAR IPS MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW KELAS V SD NEGERI 01 BEDANA KABUPATEN BANJARNEGARA (IPS STUDENT LEARNING OUTCOMES IMPROVEMENT THROUGH COOPERATIVE LEARNING MODEL TYPE V JIGSAW CLASSROOM ELEMENTARY SCHOOL DIST (Jurnal Kreatif : Jurnal Kependidikan Dasar, 2011)
Learning Process IPS at SDN 1 Bedana Kab. Banjarnegara still use the less innovative learning model, so that students are not active, without being able to criticize the concept of IPS like. This causes the students passive and low learning outcomes. Type of cooperative learning jigsaw model is one solution to resolve the issue. Formulation of the problem in this study are: 1) Does the type of cooperative learning jigsaw model student learning outcomes can be improved in? 2) Is the model of the type of cooperative learning jigsaw activity students can be increased? 3) Does the type of jigsaw model of cooperative learning activities teachers can be increased?. Classroom Action Research goal is to describe the application of the type of jigsaw cooperative learning model in teaching social studies in an effort to increase student activity and to determine the learning outcomes of students in learning social studies. Research methodologies used include the entire student class V which amounts to 27 children consisted of 15 male students and 12 female students. The variables of this study are the skills of teachers, student activities, and student learning outcomes. This study lasted for three cycles. Data collection tool that is used is observation, tests, and documentation. Analysis of the data in this class action research using descriptive analysis. In this study the type of jigsaw cooperative learning stages are as follows: 1) The teacher divides students into groups of 4-5 people consisting of the original. 2) Each student in the group had different tasks. 3) Students who received the same material gathered into a group of experts. 4) Students in the expert group discussions. 5) Students kekelompok original return and explain the results of discussions at the expert group. 6) The teacher gives a quiz to students. 7) Teachers give rewards to the group receiving the best value. The results showed achievement cycle I obtained the lowest score of 90 and 40 the highest average of 71.07 with 67.9% completeness learning, student activity score of 17.55 and earned both criteria, the activity score of 2.55 and a teacher obtained a good criterion. Cycle II, the lowest value of 45 top 100 and an average of 74.4 with a classical exhaustiveness 74.07%, the activity of the students obtained better scores 20.59 and criteria, the activity score of 2.77 and a teacher obtained a good criterion. Cycle III of the lowest 60 highest values â€‹â€‹obtained 100 and the average 85.5 and 92.5% completeness classical learning, student activity score of 3.40 is obtained and the criteria very well, the activity score of 3.44 obtained by teachers and the criteria very well. Based on the research results can be concluded that the model type of jigsaw cooperative learning can enhance the activity of students and teachers and student learning outcomes in teaching social studies class V Elementary School District 01 Bedana Banjarnegara. Jigsaw types of learning methods should be more socialized to be more understandable for the students, teachers, and all the elements of education. Keywords: Learning Outcomes, Jigsaw Cooperative Learning Model Type, Subject IPS Â